2003
DOI: 10.1096/fj.03-0501fje
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor deficiency increases vulnerability of the nigrostriatal dopaminergic system: critical role of glial nitric oxide

Abstract: Glucocorticoids (GCs) exert via glucocorticoid receptors (GRs) potent anti-inflammatory and immunosuppressive effects. Emerging evidence indicates that an inflammatory process is involved in dopaminergic nigro-striatal neuronal loss in Parkinson's disease. We here report that the GR deficiency of transgenic (Tg) mice expressing GR antisense RNA from early embryonic life has a dramatic impact in "programming" the vulnerability of dopaminergic neurons to 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). The G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(123 citation statements)
references
References 87 publications
5
117
0
1
Order By: Relevance
“…Although neuronal iNOS immunoreactivity has been reported previously (Heneka et al, 2003;Grange-Messent et al, 2004;Rodrigo et al, 2004;Small et al, 2004), its expression is certainly well documented in glia as well (Xie et al, 2002;Dehmer et al, 2004;Iravani et al, 2004;Morale et al, 2004;Wang et al, 2004). To confirm that our iNOS-mediated death was occurring via neuronally generated nitric oxide, we performed immunohistochemistry to determine which cell types in our culture were expressing iNOS.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Although neuronal iNOS immunoreactivity has been reported previously (Heneka et al, 2003;Grange-Messent et al, 2004;Rodrigo et al, 2004;Small et al, 2004), its expression is certainly well documented in glia as well (Xie et al, 2002;Dehmer et al, 2004;Iravani et al, 2004;Morale et al, 2004;Wang et al, 2004). To confirm that our iNOS-mediated death was occurring via neuronally generated nitric oxide, we performed immunohistochemistry to determine which cell types in our culture were expressing iNOS.…”
Section: Resultsmentioning
confidence: 72%
“…However, it is probable that several cell types as well as additional molecules contribute to neuronal death in vivo during similar inflammatory events. For example, astrocytes and microglia are also very effective at generating damaging oxidizing/nitrating species (Xie et al, 2002;Dehmer et al, 2004;Iravani et al, 2004;Morale et al, 2004;Wang et al, 2004). In vivo or during glia-neuron coculture paradigms, A␤-activated glia can certainly generate labile oxidizing species that contribute acutely to the resultant neuronal death (Xie et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Of special interest, astrocytes play crucial roles in the brain response to neuronal injury and plasticity (23,24,26). In particular, functional astrocytes are required to defend neurons against reactive oxygen and nitrogen species, whereas loss of astrocyte function increases neuronal vulnerability to cell death (24,26). The modulation by UCB of the expression and localization of the Mrp1 efflux pump in astrocytes, herein reported, may thus be pivotal for protecting neurons against toxic insults, such as oxidant stress (26) and UCB itself.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes defend neurons against oxidative insults (22,23) by scavenging reactive oxygen species and producing factors that induce antioxidant enzymes (22)(23)(24)(25)(26). Astrocytes also regulate growth, differentiation, and survival of neurons as part of bidirectional neuronal-glial interactions (27)(28)(29).…”
mentioning
confidence: 99%
“…In addition to oxidative stress also other mechanisms have been proposed to be involved in selective DA neuron degeneration in PD, including excitotoxicity, intracellular calcium and metal ion rise, neurofibrillary tangle formation and disruption of the cytoskeletal transport [112]. More recently, neuroinflammation and microglial activation have been implicated in the neurodegenerative process in PD, as initially suggested by McGeer et al [155] and then by several authors ( [77,89,95,97,104,102,107,148,168]). In fact, studies accumulated over the last two decades have clearly indicated the presence of an abnormal glial response in postmortem nervous system of PD patients.…”
Section: Parkinson's Disease and Neuroinflammationmentioning
confidence: 95%